Strengthening Pancasila Student Profiles Through Learning Media Infographic - Fitria Utami Putri Bintari; Rini Triastuti; Muhammad Hendri Nuryadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Education in Indonesia is making curriculum changes, from the 2013 curriculum to an independent learning curriculum. One of the characteristics of the independent learning curriculum is the formation of a Pancasila student profile which has 6 dimensions and must be present in learning activities. The purpose of this Pancasila student profile is to form students who have and are guided by Pancasila. The use of this infographic media can strengthen the Pancasila Student Profile shown in learning activities. Based on the research that has been done, it was found that strengthening the profile of Pancasila students can be done using infographic learning media. More deeply the use of infographic learning media shows more dimensions of critical reasoning, creative and mutual cooperation.